A study on the tracing of the fiber connections of the subfornical organ by using a single fluoresence labelling tracer, 4',6-Diamidino-2- Phenylindol Dihydrochloride (DAPI) (Faculty of Medicine Universitas Indonesia, 1994)
[no abstract available]